Evaluation of sublethal phyto-toxic effects of herbicides using biochemical indices - Ogeleka, D.F.; Okieimen, F.E.; Peretiemo-Clarke, B.O. (International Journal of Environment, Agriculture and Biotechnology, 2020)
The study assessed the biochemical alterations of three commonly used herbicides (Starforce®, Dragon® and Force Uron®) exposed to anon-target environmental receptor -Allium cepa L at sub-lethal levels. The oxidant activity - measured as malondialdehyde and the anti-defensive mechanism (superoxide dismutase and catalase were used to evaluate the deleterious effects of the test herbicides. At higher percentage of the test herbicides, there was elevated levels of MDA in the exposed Allium cepa Linn with respect to the control (P˂0.05). This was followed bya decrease in the antioxidant activities (SOD and CAT) as concentrations increased (P˂0.05).The study concluded that the test herbicides generated reactive oxygen species (ROS) resulting in elevated levels of lipid peroxidation, which may possibly havealtered the activities of SOD and CAT, thereby leading to oxidative stress in Allium cepa Linn at levels below and at the presumed safe limit (10% of EC50) and this should be a concern to human who are the end users of this edible non-target plant.